2019
DOI: 10.3904/kjim.2016.205
|View full text |Cite
|
Sign up to set email alerts
|

Aromatase inhibitor use is a risk factor of carotid plaque presence in endocrine-responsive breast cancer patients

Abstract: Background/Aims The aromatase inhibitors (AIs) are well known anti-hormonal therapy in endocrine-responsive breast cancer patients. It can lead to dyslipidemia and be the risk factor of cardiovascular disease due to low estrogen level. However, some recent studies comparing AIs with placebo have shown controversial results. The aim of this study was to investigate lipid profiles, measurement of carotid intima-media thickness (IMT) and the presence of plaque among endocrine-responsive breast cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Gallicchio et al investigated several vascular parameters including cIMT in a small group (n = 112) of breast cancer patients and found no significant changes after 1 year of AI use [26]. An even smaller study (n = 85) also found no difference in median cIMT when comparing BC patients treated with AI (mean duration of use 34 months) to those not receiving endocrine treatment [27]. Carotid plaques, however, were seen more frequently among AI users in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Gallicchio et al investigated several vascular parameters including cIMT in a small group (n = 112) of breast cancer patients and found no significant changes after 1 year of AI use [26]. An even smaller study (n = 85) also found no difference in median cIMT when comparing BC patients treated with AI (mean duration of use 34 months) to those not receiving endocrine treatment [27]. Carotid plaques, however, were seen more frequently among AI users in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Gallicchio et al investigated several vascular parameters including cIMT in a small group (n = 112) of breast cancer patients and found no signi cant changes after 1 year of AI use [26]. An even smaller study (n = 85) also found no difference in median cIMT when comparing BC patients treated with AI (mean duration of use 34 months) to those not receiving endocrine treatment [27]. Carotid plaques, however, were seen more frequently among AI users in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Endocrine therapy was not part of the standard treatment for patients with breast cancer in the Netherlands until the mid-1990s. However, nowadays, patients frequently receive endocrine therapy, and it has been shown that this therapy is associated with the presence of carotid plaques [ 40 ]. Also, the CMF regimen is no longer considered an optimal adjuvant chemotherapy regimen for breast cancer, but it has been the standard regimen worldwide up to the 1990s [ 39 ].…”
Section: Discussionmentioning
confidence: 99%